Nilai Pemanfaatan Limbah Kelapa Sawit untuk Pakan Ternak (Studi Kasus Pakan Ruminasia) - Sumartono, Eko; Mujiono, Mujiono; Oktapriza, Johnny; Yuliana, Fetri (Universitas Galuh, 2024)
The issue of feed has a large proportion of the sustainability of livestock businesses. On the other hand, palm fronds as post-harvest agricultural waste and bran as post-processing waste have not been utilized optimally. Even though the nutritional content contained in it is quite high. Agricultural and plantation waste by-products have good potential for use as animal feed. In order to guarantee safety and suitability, further processing and analysis is needed. Processing of raw materials is carried out in a combination (physical, chemical and biological). Preparation of feed formulations using Pearson's Quadrilateral Method. Testing is carried out in laboratories that consistently apply ISO/IEC 17025: 2017 from the National Accreditation Committee (KAN), namely the East Java Province Animal Husbandry Service. The standard test results refer to SNI 3148-2:2017 concerning Concentrate Feed for Fattening Beef Cattle. Ruminant animal feed that meets SNI 3148-2:2017 includes levels of ash, crude fat, phosphorus, TDN, aflatoxin and crude fiber. Meanwhile, the nutritional content that is close to SNI is crude protein and aNDF. The test results also showed that the content did not meet SNI, including water and calcium content. Meanwhile, fish feed (pellets) that meet SNI 01-4087-2006 contain 3 types of content including ash, crude fat and aflatoxin. The types of content that do not meet SNI are crude protein, crude fiber, phosphorus, buoyancy and pellet diameter. The estimated cost of making ruminant feed is IDR 5,986 per kilogram. Cost analysis is relevant to feed quality and daily requirements without reducing nutritional value. Further research is needed to ensure that artificial feed is more cost efficient than conventional feed.